High power, twin-band mid-infrared PPMgLN optical parametric oscillator pumped at 1.679 µm - Peng, Yuefeng; Zhang, Jianing; Wang, Yong (Optics letters, 2020)
We report on a high-power, twin-band mid-infrared (MIR) periodically poled MgO-doped ${{\rm LiNbO}_3}$LiNbO (PPMgLN) optical parametric oscillator (OPO) pumped by a near-infrared pulsed OPO with 20 kHz of repetition rate. The pump source has a central wavelength of 1.679 µm and a linewidth of 0.12 nm. The MIR OPO can be tuned from 2.74 to 2.80 µm for signal and from 4.34 to 4.19 µm for idler through raising the oven temperature from 30°C to 200°C, respectively. Under 100°C oven temperature, the OPO yielded maximum total output power of 15.4 W (2.76 µm signal plus 4.29 µm idler) with single-pass pumping configuration. The beam quality ${M^2}$M was measured to be $ \lt {2.5}$<2.5 for signal and $ \lt {4}$<4 for idler.